Research & development and long-term economic growth: A Bayesian model averaging analysis - Roman Horváth (Charles University in Prague, Institute of Economic Studies (IES), 2011)
We examine the effect of research and development (R&D) on long-term economic growth using the Bayesian model averaging (BMA) to deal rigorously with model uncertainty. Previous empirical studies investigated the effect of dozens of regressors on long-term growth, but they did not examine the effect of R&D due to data unavailability. We extend these studies by proposing to capture the R&D intensity by the number of Nobel prizes in science. Using our indicator, our estimates show that R&D exerts a positive effect on long-term growth with posterior inclusion probability of 0.25 using our preferred parameter and model priors.
Keywords: O30; O32; O10; 330; research and development; economic growth; Bayesian model averaging